1992
DOI: 10.1007/bf02887847
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effect of magnetized water on enzyme activities by potentiometric enzyme electrode method

Abstract: A very promising glutamate decarboxylase electrode, which has linear response range of 5.6 x 10(-5)-1.2 x 10(-2) mol/L. Nernstian slope of 50 mV/decade, detection limit of 3.2 x 10(-5) mol/L and response time less than 3 min, has been designed to observe and evaluate quantitatively the effect of magnetized water on enzyme activities by potentiometric enzyme electrode method. It was found that the activity of glutamate decarboxylase can increase by 30% in magnetized water. The mechanism of increased enzyme acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Similar results were found in other two studies from the same authors [59, 60]. In China, a study conducted by Yi-Long et al [61] studied the effect of magnetized water on enzyme activities and showed that the activity of glutamate decarboxylase was increased by 30% in magnetized water.…”
Section: Fluidotherapy (Fluidic Water)supporting
confidence: 87%
“…Similar results were found in other two studies from the same authors [59, 60]. In China, a study conducted by Yi-Long et al [61] studied the effect of magnetized water on enzyme activities and showed that the activity of glutamate decarboxylase was increased by 30% in magnetized water.…”
Section: Fluidotherapy (Fluidic Water)supporting
confidence: 87%
“…From a biological aspect, magnetized water has numerous applications. Supplementation with magnetized water has an anti-aging effect [44] and improves blood glucose and lymphocytes [45] in mice. In addition, growth is enhanced by magnetized water in plants [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the physiological activity of magnetized water have been reported during 1980s and 1990s, mainly in China. It has been reported that the intake of magnetized water treated ascariasis [28] or dissolved calculus [29], and increased glutamate decarboxylase activity [19]. Ma et al [19] presented the possibility that magnetized water can prevent aging and fatigue by increasing the cell membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the intake of magnetized water treated ascariasis [28] or dissolved calculus [29], and increased glutamate decarboxylase activity [19]. Ma et al [19] presented the possibility that magnetized water can prevent aging and fatigue by increasing the cell membrane permeability. In addition, some clinical cases claim that it is effective in asthma, arthritis, diabetes, and obesity, but most of the results are not based on solid science.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation